Comparison of luminescence property of gamma‐ray irradiated Tb3+‐doped and Ce3+ co‐doped potassium halide single crystals. (8th August 2016) - Bangaru, S.; Ravi, D.; Saradha, K.
Abstract: Single crystals of KCl and KBr singly and doubly doped with Tb 3 + and Ce 3 +, respectively, were successfully grown using the Bridgeman technique. This work reports the comparative luminescence behavior and optical absorption characterization of non‐irradiated and γ‐ray‐irradiated single crystals of these materials. The existing defect and the defect created by γ‐ray irradiation were monitored by optical absorption spectra. The excitation and emission spectra of these materials were measured at room temperature with a spectrofluorometer and the pertaining results were compared. The F‐band comparison was made when bleached with F‐light for 2 mins. The trap‐level changes in KCl and KBr when it is singly and doubly doped enabled us to draw conclusions on the nature of the defect and on the recombination processes involved.